2020
DOI: 10.3389/fmicb.2020.565367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rearing Conditions and Sex on Cecal Microbiota in Ducks

Abstract: The intestinal microbiome influences the health of animals. However, little is known about the impact of indoor conditions and sex on intestinal microbiome diversity and composition in ducks. The present study aimed to investigate differences in the cecal microbiome between male and female ducks reared on the floor (PY group) or in cages (LY group). We also determined the relationships between cecal microbiota composition and slaughter traits, and the expression levels of mucosal and intestinal structural gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 61 publications
7
15
2
Order By: Relevance
“…The data for all carcass traits, including LW, CW, SEW, EW, BMW, TMW, GW, and AFW, were normal, with a carcass yield, semi-eviscerated yield, and eviscerated yield of >82%, 77%, and 70%, respectively. As shown in Table 3 , the rearing method did not significantly affect slaughter performance, including carcass yield, semi-eviscerated yield, eviscerated yield, breast muscle yield, thigh muscle yield, and lean meat yield ( P > 0.05), which is consistent with the results of Zhu et al. (2020) .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The data for all carcass traits, including LW, CW, SEW, EW, BMW, TMW, GW, and AFW, were normal, with a carcass yield, semi-eviscerated yield, and eviscerated yield of >82%, 77%, and 70%, respectively. As shown in Table 3 , the rearing method did not significantly affect slaughter performance, including carcass yield, semi-eviscerated yield, eviscerated yield, breast muscle yield, thigh muscle yield, and lean meat yield ( P > 0.05), which is consistent with the results of Zhu et al. (2020) .…”
Section: Resultssupporting
confidence: 85%
“…Thus, the cage pattern may be more efficient and can improve the growth performance of small-sized meat ducks compared with the floor rearing system. Similarly, Zhu et al. (2020) found that the final BW of both male and female Gaoyou ducks was higher in the cage group than in the floor group.…”
Section: Resultsmentioning
confidence: 77%
“…This means that the meat production performance of the goose in CR is higher than in FR. This contradicts other studies, they found that ducks in FR had better meat production performance than CR ( Zhu et al, 2020 ). The differences may be caused by the change in feed intake of geese.…”
Section: Discussioncontrasting
confidence: 66%
“…Compared with the traditional rearing system, the dryland rearing on netting floors ( DRNF ) system changed intestinal microbial abundance and enhanced the immune ability of Shaoxing ducks ( Zhao et al, 2019 ). Compared with floor rearing, cage rearing changed the cecal microbial abundance of ducks and affected cecal mucosa gene expression ( Zhu et al, 2020 ). Therefore, we hypothesized that the rearing systems might also alter geese's physiological functions and production performance.…”
Section: Introductionmentioning
confidence: 99%
“…The most common class of Cyanobacteria detected in Kirtland's Warblers, Oxyphotobacteria , is an oxygenic phototroph (Shih et al, 2017). Oxyphotobacteria has previously been described in an avian host but is unlikely to provide a host associated function, suggesting the presence of this class is transient and the result of environmental sourcing (Zhu et al, 2020). In addition to Oxyphotobacteria , we detected several common environmental, soil‐associated bacterial genera, including Acitomycetospora , Aureimonas , Solirubrobacter and Nocardioides , as more abundant in birds in The Bahamas (Janssen, 2006; Topp et al, 2000).…”
Section: Discussionmentioning
confidence: 99%